Determinant Factors of Low Elderly Visits to Sebotok Village Posyandu, Labuhan Badas Unit II Primary Health Center - Harmili, Harmili; Rafi'ah, Rafi'ah; Sarkasi, Rosnani; Abd Hamid, Abdul Alif (STIKES Adi Husada, 2024)
The proportion of elderly individuals in Indonesia rose from 7.57 percent in 2012 to 10.48 percent in 2022, with projections indicating a continued increase to 19.9 percent by 2045. This demographic shift underscores the need for focused attention on the aging population. This study aims to identify the factors influencing low visitation rates of the elderly to the Posyandu (Integrated Health Post) in Sebotok Village, under the purview of the Labuhan Badas Unit II Primary Health Center. Employing an analytical research design with a cross-sectional approach, the study surveyed 46 respondents selected through purposive sampling, utilizing a questionnaire as the primary instrument. Statistical analysis employed Fisher's exact test, revealing significant correlations between posyandu accessibility (p-value = 0.000), knowledge (p-value = 0.008), and family support (p-value = 0.000) with elderly visitation rates. However, no significant relationships were found between the services provided by health workers (p-value = 0.536) or posyandu volunteers (p-value = 0.536) and elderly visitation. Recommendations include enhancing education initiatives aimed at families and the elderly to emphasize the importance of regular health check-ups for the elderly population.